Climate Change and Water Sources: A Case of Phobjikha and Gangtey Gewog, Wangdue Phodrang Dzongkhag, Bhutan - Namgay Wangmo; Jambay; Ugyen Dorji; Om Katel (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
Water is a fundamental resource and for millions of people living in the Himalayas, springs are their only source of water for household and farming. To meet the water requirements, the communities depend on rain-fed springs which are highly sensitive to climate change. Rural communities in developing countries would be the most affected among other communities around the world as they have limited resources at their disposal. The objective of this study is to document the local people's awareness of climate change and their knowledge of water source dynamics constrained by climate change impacts in Phobjikha and Gangtey Gewogs, one of the Ramsar sites in Bhutan. A total of 248 households were interviewed using structured questionnaires employing simple random sampling techniques. Chi-Square test of independence was conducted. Results indicate that education is associated with awareness and water source dynamics. However, the majority of the residents do not have a clear understanding of how climate change affects water sources and how those sources should be protected. We recommend the relevant agency provide education and awareness on climate change impacts and training on water sources protection and management to local people. This would not only help local people enhance their resilience against climate change impacts but also protect their local resources for sustainable livelihoods.  Also, Phobjikha and Gangtey are important locations to study climate change impacts in high altitude areas concerning both local peoples' adaptation strategies and dynamics of water as vital natural resources.